2016
DOI: 10.1016/j.rpped.2016.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Estágios de mudança de comportamento para atividade física em adolescentes catarinenses: prevalência e fatores associados

Abstract: A large proportion of adolescents are in the pre-adoption stages and most of these have the intention to start regular physical activity. With the exception of school shift, the assessed variables were associated with stages in different ways, showing different profiles in relation to sociodemographic and economic characteristics in each subgroup.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
2
3
1
3
Order By: Relevance
“…The majority of adolescents were in the maintenance stage and the minority was in the pre-contemplation stage. These findings corroborate the results of research conducted with adolescents from Pernambuco 11 and Santa Catarina 4,10,[12][13][14] , but there were differences between studies in the prevalence verified at each stage. Partially divergent results were found in a survey with Belgian 15 and US adolescents 17 , since most of them were in the maintenance stage; however, the action stage was the least frequent.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…The majority of adolescents were in the maintenance stage and the minority was in the pre-contemplation stage. These findings corroborate the results of research conducted with adolescents from Pernambuco 11 and Santa Catarina 4,10,[12][13][14] , but there were differences between studies in the prevalence verified at each stage. Partially divergent results were found in a survey with Belgian 15 and US adolescents 17 , since most of them were in the maintenance stage; however, the action stage was the least frequent.…”
Section: Discussionsupporting
confidence: 89%
“…Girls were more likely of being in the action, preparation, contemplation and pre-contemplation stages compared to boys, corroborating other national surveys 4,10 . According to Silva et al 4 , the chance of boys practicing regular PA is higher compared to girls. However, the findings of the present study also suggest that girls showed greater intention to move to more active behavior.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations